Recycled oceanic gabbro produced the depleted component in hotspot magma from the Comei large igneous province in the Kerguelen mantle plume - Long Chen; Yaying Wang; Ian Somerville; Yuan Zhong; Xiaohui Li; Dongyong Li; Jianghong Deng; Shengyao Yu; Guochao Sun; Zifu Zhao; Sanzhong Li (Communications Earth & Environment)
Abstract Depleted components in hotspot magma sources remain enigmatic. Zircon δ18O values (3.97–4.80‰, average 4.38‰) from depleted gabbros in the Comei province (Kerguelen plume) are lower than mantle zircons, correlating negatively with 206Pb/U238ages. Combined with ultradepleted Hf isotopes, this excludes hydrothermal alteration or crustal contamination, instead indicating mixing of heterogeneous mantle magmas with light-oxygen, Hf-depleted components. Elevated Sc/Nb and Y/Nb ratios preclude upper mantle entrainment, while light δ¹⁸O contradicts ancient melting residues. We propose these components originate from recycled high-temperature hydrothermally altered gabbroic oceanic crust, which underwent melt extraction during subduction before incorporation into the plume. Gradual δ¹⁸O increases reflect progressive consumption of these components during melting with ambient mantle. This study highlights recycled gabbroic crust’s role in generating depleted hotspot magmas. Preservation and emergence of low δ¹⁸O and depleted geochemical signatures requires limited mixing with enriched/high-δ¹⁸O materials, as these fragile signatures are easily masked by geochemical overprinting.